Komi can't communicate. Volume 5 - Oda, Tomohito, 1991- (Shōnen Sandē komikkusu., 2020)
"Socially anxious high school student Shoko Komi's greatest dream is to make some friends, but everyone at school mistakes her crippling social anxiety for cool reserve! Luckily she meets Tadano, a timid wallflower who decides to step out of his comfort zone in order to help her achieve her goal of making 100 friends... Komi's friendship quest just hit its first major obstacle--the green-eyed monster! Tadano and a girl named Onemine have been hanging out a lot lately, and Komi doesn't know how to deal with her sudden flood of jealousy. She can't explain what's wrong, so she ends up spying on them from the shadows. Will her creepy peeping lose her a chance at a new friend and push Tadano away?"--Provided by publisher.